A Photocleavable Masked Nuclear‐Receptor Ligand Enables Temporal Control of C. elegans Development1. (21st January 2014) - Judkins, Joshua C.; Mahanti, Parag; Hoffman, Jacob B.; Yim, Isaiah; Antebi, Adam; Schroeder, Frank C.
Abstract The development and lifespan of C. elegans are controlled by the nuclear hormone receptor DAF‐12, an important model for the vertebrate vitamin D and liver X receptors. As with its mammalian homologues, DAF‐12 function is regulated by bile acid‐like steroidal ligands; however, tools for investigating their biosynthesis and function in vivo are lacking. A flexible synthesis for DAF‐12 ligands and masked ligand derivatives that enable precise temporal control of DAF‐12 function was developed. For ligand masking, photocleavable amides of 5‐methoxy‐N‐methyl‐2‐nitroaniline (MMNA) were introduced. MMNA‐masked ligands are bioavailable and after incorporation into the worm, brief UV irradiation can be used to trigger the expression of DAF‐12 target genes and initiate development from dauer larvae into adults. The in vivo release of DAF‐12 ligands and other small‐molecule signals by using photocleavable MMNA‐masked ligands will enable functional studies with precise spatial and temporal resolution.